Impact of a 36-hour Nonstop Training Course on Academic, Physical, and Mental Skills as well as Psychological Stress Perception in Cardiac Surgery Residents - Caldonazo, Tulio; Kirov, Hristo; Schneider, Ulrich; Beckmann, Andreas; W., K.; Weber, Günter; Iglauer-Sander, Regina; Färber, Gloria; Doenst, Torsten; and on behalf of all Strong GermaN HeaRTS Participants (The Thoracic and Cardiovascular Surgeon, 2023)
Background Making the right decision in stressful situations is required for goal-oriented action in cardiac surgery. Current labor laws prevent residents to be subjected to situations that test their stress tolerance. These situations often occur only later in the career. We simulated such conditions in a structured non-stop 36-hour cardiac surgical training course and assessed the participant's performance.Methods Fourteen advanced residents/junior staff surgeons were selected. The course was conducted in collaboration with the national antiterror police forces that provided coaching for teamplay, leadership, and responsibility awareness. The candidates attended graded and evaluated workshops/lectures and performed academic and surgical tasks. Psychological and surgical skill assessments were conducted at times 0, 12, 24, 36 hours.Results Progressive reductions in individual motivation, associated with increased stress and irritability levels, worsening mood, and fatigue were observed. Long- and short-term memory functions were unaffected and practical surgical performance even increased over time.Conclusion Among the candidates, 36 hours of sleep deprivation did not lead to relevant changes in the skills required from a cardiac surgeon in daily life. Importantly, group dynamics substantially improved during the course, suggesting advances in the perception of responsibility and teamwork.
Keywords: cardiac surgery; cardiovascular medicine; surgical training; mental skills